2016
DOI: 10.7322/abcshs.v41i2.873
|View full text |Cite
|
Sign up to set email alerts
|

A influência do conhecimento na atitude frente à vacina contra o Papilomavírus Humano: ensaio clínico randomizado

Abstract: Introdução: O Papilomavírus humano (HPV) está associado às doenças sexualmente transmissíveis (DSTs) e à carcinogênese do trato genital inferior. Objetivo: Avaliar o conhecimento prévio e o papel da ação educativa sobre a atitude em relação à vacinação para Papilomavírus Humano (HPV). Métodos: Estudo de intervenção, tipo ensaio-clínico randomizado com 200 mulheres de 18 a 30 anos, divididas em dois grupos submetidos a um questionário para avaliar o conhecimento prévio sobre o HPV e sua vacina, e a atitude para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
7
0
12
Order By: Relevance
“…13,[20][21] Also, correction and distribution of vaccine doses are required to achieve homogeneous coverage within the Midwest Region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[20][21] Also, correction and distribution of vaccine doses are required to achieve homogeneous coverage within the Midwest Region.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the objective is to disseminate information about the quality and access of young people to the topic, considering the extreme importance of the family and the school environment as reliable sources of sexual education orientation. [13][14] Some studies have shown that the ideal strategy to ensure good vaccine coverage is based on increased adherence to immunization programs. The main strategy consists of the partnership with the public and private schools and Units of Primary Care to Family Health (UABSF), guaranteeing information and clarification of the target public and those responsible.…”
mentioning
confidence: 99%
“…33 The educational action to promote vaccination against HPV, when well planned and performed, has the function of increasing the knowledge of individuals, generating appropriate attitudes and enabling behavior change, and can be an important tool for the success of vaccination campaigns in society, with the aim of combating the virus and the various types of neoplasms that it causes from improving adherence. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Utilizou-se o instrumento de pesquisa "Conhecimento, atitude e prática sobre a vacinação", validado e pré-testado (Pereira et al, 2016). O instrumento é subdividido em 6 seções de perguntas.…”
Section: Metodologiaunclassified